Actinic keratosis treated by topical Aloe barbadensis Mill. (Aloe Vera) leaf gel - Direito, Rosa (2022)
Aloe vera is a cactus-resembling, succulent, watery plant, extensively used by the cosmetic and food industries[1]. Actinic keratosis, a dysplastic skin lesion commonly found in low Fitzpatrick skin type individuals[2] associated with chronic UV exposure[3,4], is defined by a scaly, keratotic or pigmented papule on an erythematous base[5]. The precursor to skin field cancerization is actinic keratosis, which is an area of photodamaged skin containing subclinical genetic changes, a direct consequence of intraepithelial UV-induced damage[6,7]. Actinic keratosis, as a precancerous lesion, can develop into an invasive squamous cell carcinoma (ISCC)[6]. There is no way to predict which lesions will progress to ISCC, with guidelines recommending treatment of all actinic keratosis lesions[8- 11]. Field-directed therapies are used to treat multiple actinic keratosis lesions and contiguous field cancerization subclinical lesions[12]